Prix Meret Oppenheim 2001-2002 : Interviews - Banz, Stefan (Bern : Bundesamt für Kultur, 2006)
Rüegg, Ilona ; Steinmann, George ; Kamm; Peter ; Anüll, Ian ; Brunner, Hannes ; Levi, Renée ; RELAX ; Burki, Marie-José
boek